Evaluation of ovarian reserve in Hashimoto's thyroiditis. (6th June 2014) - Tuten, Abdullah; Hatipoglu, Esra; Oncul, Mahmut; Imamoglu, Metehan; Acikgoz, Abdullah Serdar; Yilmaz, Nevin; Ozcil, Mustafa Dogan; Kaya, Baris; Misirlioglu, Ali Mesut; Sahmay, Sezai
Abstract: Human ovary is commonly the target of an autoimmune attack in cases of organ- or non-organ-specific autoimmune disorders. Hashimoto's thyroiditis (HT) is likely to be associated with ovarian dysfunction and diminished ovarian reserve. In this study, we aimed to evaluate the possible negative association between this significantly prevalent autoimmune disease and the ovarian reserve. Thirty-two premenopausal women with primary hypothyroidism, who under replacement therapy with thyroxine were recruited. Forty-nine healthy female subjects who had normal anti-thyroid antibody levels and were comparable with the HT group in terms of age and BMI values, comprised the control group. There was no statistically significant difference between the study and the control patients in terms of antral follicle count. Serum anti-Müllerian hormone (AMH) levels were significantly higher in woman with HT compared to the control group. The results of this study found no impairment in ovarian reserve parameters of patients with HT. Interestingly, the results revealed a significant increase in serum AMH levels of the patients with HT compared to controls. Hashimoto's thyroiditis may share a common etiologic linkage with polycystic ovary syndrome; therefore, leading to elevated serum AMH levels, which we are currently unable to define elaborately.